1996
DOI: 10.1002/elan.1140080606
|View full text |Cite
|
Sign up to set email alerts
|

Development of an amperometric enzyme biosensor for the determination of the antioxidant tert‐butylhydroxyanisole in a medium of reversed micelles

Abstract: A biocdtalytic scheme, based on the enzyme tyrosinase, has been developed for the determination of the antioxidant ferfbutylhydroxyanisole (BHA) in food samples. Reversed micelles formed with ethyl acetate as organic solvent, dioctyl sulfosuccinate (AOT) as emulsifying agent, and phosphate buffer of pH 7.4 as aqueous phase, has been employed as the working medium. The potential applied to the tyrosinase electrode, as well as the temperature of the working reversed micelle, the percentage of aqueous phase, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

1998
1998
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 12 publications
0
5
0
Order By: Relevance
“…Another alternative is to monitor the reaction of 16-ArN 2 + with an antioxidant electrochemically. Following phenolic antioxidant reactions electrochemically is now routine (47), including in reverse micelles (48) and TBHQ in emulsions (49), and loss of arenediazonium ion has been monitored electrochemically (50)(51)(52), including the reaction of 16-ArN 2 + with TBHQ in octane/H 2 O/C 12 E 6 emulsions (unpublished results). Electrochemical methods also permit continuous monitoring of reactions that are substantially faster than those monitored by the sampling technique and rapid analysis of the data to obtain k obs .…”
Section: Discussionmentioning
confidence: 99%
“…Another alternative is to monitor the reaction of 16-ArN 2 + with an antioxidant electrochemically. Following phenolic antioxidant reactions electrochemically is now routine (47), including in reverse micelles (48) and TBHQ in emulsions (49), and loss of arenediazonium ion has been monitored electrochemically (50)(51)(52), including the reaction of 16-ArN 2 + with TBHQ in octane/H 2 O/C 12 E 6 emulsions (unpublished results). Electrochemical methods also permit continuous monitoring of reactions that are substantially faster than those monitored by the sampling technique and rapid analysis of the data to obtain k obs .…”
Section: Discussionmentioning
confidence: 99%
“…Electrochemical methods for the determination of antioxidant activity based on the application of biosensors (Ruiz et al 1996) to measure antioxidant properties of tert-butylhydroxyanisole and the cyclic voltammetry (Chevion et al 1997) to study the efficiency of some low molecular weight antioxidants are reported. DPPH method has been used to evaluate the antioxidant ability of phenol compounds (Sanchez-Moreno et al 1998).…”
Section: Developments In Dpph Methodsmentioning
confidence: 99%
“…There were also reports of electrochemical methods for the measurement of antioxidant activity which are based on biosensors using cyclic voltammetry as a detection technique [ 106 ] to measure the antioxidant capacity of tert-butyl-hydroxyanisole [ 107 ]. These were used to study the efficiency of some antioxidants with a low molecular weight.…”
Section: Chemical Tests Determining Antioxidant Activitymentioning
confidence: 99%